2021
DOI: 10.1002/ptr.7344
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin ameliorates hepatic lipid accumulation by enhancing autophagy and suppressing IRE1α/XBP1 pathway

Abstract: Nonalcoholic fatty liver disease is the most prevalent liver disease characterized by excessive lipid accumulation in hepatocytes. Endoplasmic reticulum (ER) stress and autophagy play an important role in lipid accumulation. In this study, scutellarin (Scu) was examined in palmitic acid–treated HepG2 cells and C57/BL6 mice fed a high‐fat diet (HFD). Scu reduced intracellular lipid content and inhibited sterol regulatory element binding protein‐1c (SREBP‐1c)‐mediated lipid synthesis and fatty acid translocase‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Our data showed that inhibiting IRE1α not only significantly weakened the effects of DHA on increasing the transcription of lipolysis and PKA pathway-related genes but also reduced TG content. A related study revealed that scutellarin ameliorates hepatic lipid accumulation by suppressing the IRE1α/XBP1 pathway ( Zhang et al., 2022 ). However, inhibiting IRE1α had no effect on the Zn-mediated increase in HSL activity and a reduction in the TG content ( Song et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that inhibiting IRE1α not only significantly weakened the effects of DHA on increasing the transcription of lipolysis and PKA pathway-related genes but also reduced TG content. A related study revealed that scutellarin ameliorates hepatic lipid accumulation by suppressing the IRE1α/XBP1 pathway ( Zhang et al., 2022 ). However, inhibiting IRE1α had no effect on the Zn-mediated increase in HSL activity and a reduction in the TG content ( Song et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy revealed that after liraglutide treatment, the autophagy rate increased, the number of fat vacuoles decreased in the high-fat diet group, and p62 expression levels decreased significantly while those of LC3-II increased significantly. Zhang et al [ 43 ] treated HepG2 liver cells with palmitic acid and found that the TG levels increased significantly; the protein expression of the ERS markers GRP78, p-PERK, ATF6, p-IRE1 α , and XBP1s also increased significantly; the expression of the autophagy markers Beclin-1 and LC3-II/I decreased; the expression of p62 increased. After scutellarin intervention, the TG expression levels and the protein expression levels of the ERS markers GRP78, p-PERK, ATF6, p-IRE1 α , and XBP1s all decreased significantly, and the expression levels of the autophagy markers Beclin-1 and LC3-II/I increased, and those of p62 decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagic activity can alleviate ER stress through the breakdown of excessive unfolded proteins. Baicalin, for example, can suppress ER stress via downregulating SREBP-1C and enhancing hepatic autophagic activity, thereby preventing the accumulation of lipids within the liver ( Zhang et al, 2022 ). While studies have reported intermittent hypoxia to drive enhanced myocardial autophagy as an adaptive response to ER stress and apoptosis ( Chang et al, 2019 ), such work was focused on the short-term outcomes associated with intermitted hypoxia rather than using a CIH model system.…”
Section: Discussionmentioning
confidence: 99%